Answer:
I D K GUESS ITS 1 2 4 I GUESS THINKING
Step-by-step explanation:
Answer:
<h3>Adjacent angles or Supplementary angles I am not sure
tho:)</h3>
Step-by-step explanation:
Answer:
(3,4)
Step-by-step explanation:
Answer:
x=4
Step-by-step explanation:
-2(x+2)=-12
x+2=-12/-2
x+2=6
x=6-2
x=4
Given multiplication:
(3√6 - √2)(4√2 - √6)
= 3√6(4√2-√6)-√2(4√2-√6)
= 3√6*4√2 - 3√6*√6 - √2*4√2 + √2*√6
= 12√12 -3√(6*6) -4√(2*2) + √(2*6)
= 12√(4*3) - 3√(36) - 4√(4) + √(12)
= 12*2√3 - 3*6 - 4*2 + 2√3
= 24√3 - 18-8 +2√3
= 24√3 + 2√3 - 18-8
= 26√3 - 18-8
= 26√3 - 26
= 26(√3-1).
<u>Answer</u><u>:</u><u>-</u> (3√6 - √2)(4√2 - √6) = 26(√3-1)
<u>also</u><u> read</u><u> similar</u><u> questions</u><u>:</u> Multiply. −3 2/3⋅(−2 1/4) ? −8 1/4 −6 1/6 6 1/6 8 1/4....
brainly.com/question/18369667?referrer
what is the simplified form of 6^square root of x multiplied by 6^square root of x multiplied by 6^square root of x multiplied by 6^square root of x? 1. x^2/3 2...
brainly.com/question/25224153?referrer